Pengaruh Model Pembelajaran Cooperative Learning Tipe Jigsaw terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Peserta Didik Kelas XII SMK N 1 Siatas Barita Tahun Pembelajaran 2023/2024 - Desi Wulandari Siahaan; Rusmauli Simbolon; Ordekoria Saragih; Hasudungan Simatupang; Andar Pasaribu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The research aims to determine whether there is a positive and significant influence in the use of the jigsaw type copperative learning model on the active learning of Christian Religious Education and Character in class XI students at SMK Negeri 1 Siatas Barita for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the jigsaw type cooperative learning model on the active learning of Christian Religious Education and Characteristics of class XI students at SMK Negeri 1 Siatas Barita for the 2023/2024 academic year. The population of class XI students at SMK Negeri 1 Siatas Barita Learning 2023/2024 who are Protestant Christians is 325 people. The research sample using random sampling technique was 18% of the total population, namely 58 people. The research instrument is a closed questionnaire. The results of data analysis obtained: The value rcount=0.673>rtabel=0.254 and tcount=6.809>ttable=2.00324 shows that there is a positive and significant relationship between the jigsaw type cooperative learning model and students' active learning in Christian Religious Education and Character. Regression equation . The determination test revealed that the magnitude of the effect was 45.29%. Hypothesis test Fcount=46.479>Ftable=3.15 then H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. The research concluded that there was a positive and significant influence between the jigsaw cooperative learning model on the activeness of learning in Christian Religious Education and Character in class XI students at SMK Negeri 1 Siatas Barita for the 2023/2024 academic year.